PEDAGOGICAL CLASSIFICATION OF MASSIVE OPEN DISTANCE COURSES - Baсurovska, Ilona V. (Educological discourse, 2016)
The author of the article outlines pedagogical classification of massive open distance courses based on behaviorist and connectionist approaches; defines pedagogical features of such massive open distance courses; analyzes the classification of types of massive open distance courses and defines their characteristics; points out advantages and disadvantages of massive open distance courses; forms tasks of open distance courses projects.